Comparative analysis of immigration processes in Canada and Germany: empirical results from case studies in the health and IT sectors - Annen, Silvia [Verfasser] (My University, 2024)
„Twelve qualitative case studies in German and Canadian hospitals and IT companies were used in this mixed-methods study analysing the labour market outcomes of immigrants. The reported case studies investigate the immigrants’ recognition, integration process and the usability of foreign qualifications, skills and work experiences in the labour market. Furthermore, the strategies and rationales of employers and employees within the recruiting process are analysed. Here, the focus lies on the transferability and obstacles of cultural and social capital across country borders as well as the relevant framework conditions. This paper refers to Bourdieu’s approach towards different types of capital as well as the rational choice theory. The results demonstrate that immigrants in both countries face more obstacles accessing the labour market within the health sector than within the IT sector. The context of the recruiting situation strongly affects the strategies and behaviour of the employers or the recruiters. Within these sector- and country-specific confines, individual factors determine the immigrants’ labour market success. Furthermore, the sector and the country affect the relevance of each individual factor in the recruiting process.“ (author’s abstract; BIBB-Doku)
Keywords: P 1.5 Migranten; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 1.2.4.2.8 Gesundheits-, Veterinär- und Sozialwesen; I 2.3.2 Nordamerika; I 2.1 Deutschland; 370; Einwanderer; Ausländischer Arbeitnehmer; Auslandsqualifikation; Anerkennung; Berufliche Integration; Gesundheitswesen; Informationswirtschaft; Internationaler Vergleich; Bundesrepublik Deutschland; Kanada